Bacterial Metabolic Potential and Micro-Eukaryotes Enriched in Stony Coral Tissue Loss Disease Lesions - Rosales, Stephanie M.; Huebner, Lindsay K.; Clark, Abigail S.; McMinds, Ryan; Ruzicka, Rob R.; Muller, Erinn M. (Frontiers in Marine Science, 2022)
The epizootic disease outbreak known as stony coral tissue loss disease (SCTLD) is arguably the most devastating coral disease in recorded history. SCTLD emerged off the coast of South Florida in 2014 and has since moved into the Caribbean, resulting in coral mortality rates that have changed reef structure and function. Currently, the cause of SCTLD is unknown, but there is evidence from 16S rRNA gene sequencing and bacterial culture studies that the microbial community plays a role in the progression of SCTLD lesions. In this study, we applied shotgun metagenomics to characterize the potential function of bacteria, as well as the composition of the micro-eukaryotic community, associated with SCTLD lesions. We re-examined samples that were previously analyzed using 16S rRNA gene high-throughput sequencing from four coral species: Stephanocoenia intersepta, Diploria labyrinthiformis, Dichocoenia stokesii, and Meandrina meandrites. For each species, tissue from apparently healthy (AH) corals, and unaffected tissue (DU) and lesion tissue (DL) on diseased corals, were collected from sites within the epidemic zone of SCTLD in the Florida Keys. Within the micro-eukaryotic community, the taxa most prominently enriched in DL compared to AH and DU tissue were members of Ciliophora. We also found that DL samples were relatively more abundant in energy-efficient pathways like the pentose phosphate pathways. While less energy-efficient processes were identified, there were also a relatively higher abundances of nucleotide biosynthesis and peptidoglycan maturation pathways in diseased corals compared to AH, which suggests there was more bacteria growth in diseased colonies. In addition, we generated 16 metagenome-assembled genomes (MAGs) belonging to the orders Pseudomonadales, Beggiatoales, Rhodobacterales, Rhizobiales, Rs-D84, Flavobacteriales, and Campylobacterales, and all MAGs were enriched in DL samples compared to AH samples. Across all MAGs there were antibiotic resistance genes that may have implications for the treatment of SCTLD with antibiotics. We also identified genes and pathways linked to virulence, such as nucleotide biosynthesis, succinate dehydrogenase, ureases, nickel/iron transporters, Type-1 secretion system, and metalloproteases. Some of these enzymes/pathways have been previously targeted in the treatment of other bacterial diseases and they may be of interest to mitigate SCTLD lesion progression.